2019
DOI: 10.15446/dyna.v86n210.72880
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of different factors on the ultrasound assisted extraction of phenolic compounds of the pea pod

Abstract: The pea pod is a by-product that possesses several bioactive compounds. The effect of temperature, time, solid-liquid ratio and ethanol concentration on the ultrasonic assisted extraction of phenolic compounds were studied. A 2K factorial design was used and through ANOVA analysis the effect of each process variable was determined. Total phenols were analyzed by the Folin Ciocalteu method. The results showed that the temperature did not affect significantly the extraction of total phenols, however extraction t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Studies have shown that solid particles tend to aggregate quickly in their suspensions when the solids mass increases [10]. Consequently, increasing CaCO 3 particles aggregation with increasing eggshell mass caused the eggshell particles to settle quickly, impeding sonochemical process efficiency at higher eggshell concentrations [40,43]. Moreover, the 1 transfer principle states that the increasing concentration gradient between the substance and the solvent is the driving factor for mass transfer [40].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies have shown that solid particles tend to aggregate quickly in their suspensions when the solids mass increases [10]. Consequently, increasing CaCO 3 particles aggregation with increasing eggshell mass caused the eggshell particles to settle quickly, impeding sonochemical process efficiency at higher eggshell concentrations [40,43]. Moreover, the 1 transfer principle states that the increasing concentration gradient between the substance and the solvent is the driving factor for mass transfer [40].…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, increasing CaCO 3 particles aggregation with increasing eggshell mass caused the eggshell particles to settle quickly, impeding sonochemical process efficiency at higher eggshell concentrations [40,43]. Moreover, the 1 transfer principle states that the increasing concentration gradient between the substance and the solvent is the driving factor for mass transfer [40]. Hence, increasing the eggshell mass causes rapid saturation of the DMF solvent, which reduces the efficiency of solids dispersion and accordingly decreases the sonochemical process efficiency [40,43].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations